Penerapan Pembelajaran Mendalam (Deep Learning) pada Fase Bdi SD Negeri 81 Palembang sebagai Strategi Penguatan Kurikulum Merdeka - Ade Rahmadania Sazidah; Gladys Esakya Putri; Miftahul Rahma Salsabila; Zahra Ramadhani (Yayasan Al-Afif, 2026)
The Merdeka Curriculum demands meaningful, student-centered learning; however, in practice, many elementary school teachers have yet to optimally implement innovative instructional approaches that foster higher-order thinking skills. The core problem of this study is how Deep Learning strategies can be effectively applied to Phase B students at SD Negeri 81 Palembang to support the Merdeka Curriculum implementation. This study employed a descriptive qualitative approach with a case study design within the framework of the Teaching Practicum Program (PLP). Students served as participatory observers and instructional implementers. Data were collected through participatory observation, semi-structured interviews, and instructional document analysis. Data validity was ensured through source and technique triangulation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña (2014), comprising data condensation, data display, and conclusion drawing. The findings indicate that Deep Learning implementation in Phase B significantly improved higher-order thinking skills, active student engagement, and character development aligned with the Pancasila Student Profile. Teachers successfully transitioned from instructors to facilitators designing project-based, inquiry-driven, and reflective learning experiences. Challenges include limited teacher understanding, scarce adaptive instructional materials, and the need for a supportive school ecosystem. This study concludes that Deep Learning is an effective strategy for strengthening Merdeka Curriculum implementation in elementary schools, and PLP activities serve as a valid context for examining learning phenomena contextually.